«Era di pietra la sua bellezza». Capri, mitografia di un luogo - Eugenio Zito (EtnoAntropologia)
In the article I present, according to a cultural studies approach that includes the use of literary sources and images, a mythographical profile, although necessarily brief and not exhaustive, about the island of Capri in the bay of Naples, prodigy of natural beauty out of time, as a result of a singular combination of stone, sky, sea and light. This profile, giving back some features of its historical and cultural identity and the complex relationships that have crossed its land over time, by producing diverse and unique representations and narrations, lets discuss this Mediterranean island as anthropological place in the meaning that Marc Augé gives it. Finally, it is highlighted its recent transformation, coinciding with pervasive processes of globalization of the economy and culture of the past three decades, towards a possible nonplace.